APPLICATION OF THE PROBLEM BASED LEARNING MODEL TO INCREASE CREATIVITY AND LEARNING OUTCOMES IN ECONOMICS SUBJECTS FOR CLASS XI IPS STUDENTS AT SLUA SARASWATI 1 DENPASAR ACADEMIC YEAR 2022/2023 - I.G.A Laksmi Dewanti,SE. (Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia, 2023)
One educational problem that can affect student learning achievement is the low interest and creativity of students to take part in the learning process caused by the use of learning models that are less varied and only teacher-centered. This study aims to determine the application of problem-based learning models to improve economic learning achievement IPS XI grade students at SMA PGRI Blahbatuh. This type of research is collaborative classroom action research. The results of this study indicate that the application of problem-based learning models can improve learning creativity and economic learning outcomes of XI IPS students at SMA PGRI Blahbatuh Academic Year 2022/2023. The initial reflection showed that the average economic learning outcomes only reached 70, 70% absorbed data, and classical completeness was 32.25%. In the first cycle the average economic learning outcomes experienced an increase reaching 73.77, absorption of 73.77%, and classical completeness was 67.74%, but some students still got scores below the KKM, so researchers held the second cycle and on average Student learning outcomes in the second cycle increased to 78.48, with absorption of 78.48% and classical completeness reaching 87.09%. For the average score of learning creativity of students in the first cycle reached 30.32% with the category quite active, and experienced an increase in the second cycle to 93.54% with the active category.